2022
DOI: 10.1016/j.jpedsurg.2021.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term outcomes after pediatric redo fundoplication

Abstract: Background: Redo fundoplication (RF) is the most common surgical treatment for recurrent gastroesophageal reflux disease (GERD) in children, but outcomes after RF are rarely reported. The aim of this study was to assess short-and long-term outcomes after RF in childhood. Methods: The study is a follow-up study of patients undergoing RF from 2002 to 2020 at a teriary care center. Patients/parents were sent questionnaires recording symptoms of recurrent GERD, troublesome side-effects and satisfaction. Retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The author commented that it was likely that the stomach tissue was partially devitalized during the previous operations, resulting in weak areas that were more susceptible to injury. Conversely, in the series of redo surgeries collected by Kvello et al [ 11 ], half of the patients experienced early postoperative complications. A third of complications were major, with two patients requiring blood transfusions due to intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The author commented that it was likely that the stomach tissue was partially devitalized during the previous operations, resulting in weak areas that were more susceptible to injury. Conversely, in the series of redo surgeries collected by Kvello et al [ 11 ], half of the patients experienced early postoperative complications. A third of complications were major, with two patients requiring blood transfusions due to intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic redo surgeries are particularly demanding procedures. The instability of the camera platform, the limited motion of the laparoscopic instruments and two-dimensional (2D) imaging represent a challenge for pediatric surgeons, especially when recurrent hiatal hernias and dense postoperative adhesions significantly alter the anatomy of the esophagogastric junction [ 8 , 9 , 10 , 11 ]. These cases are also associated with the risk of bleeding from the liver and gastric vessels, injury to the vagus nerve, and organ perforation [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fundoplication is currently practised as the operation of choice for treating GORD where medical treatment has been unsuccessful. However, literature is replete with evidence of recurrence of GORD following fundoplication [1,3,4,5,7,9,15,16]. Our previous published studies by Kimber and Spitz et al [5] found redo fundoplication failed to resolve the preoperative symptoms in 20%, with 5/66 children requiring a third fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…The chance of success is likely to decrease with every further attempt of fundoplication especially in neurologically impaired children who are more susceptible to post-operative complications [13]. In view of paucity of randomised studies [14,15,16] on long term outcomes of anti-reflux interventions, it is important to explain the pros and cons to the family on individual case by case basis.…”
Section: Discussionmentioning
confidence: 99%
“…“Re-do” surgery is required in a range of patients between 6% and 14% at 20–36 months of follow-up. Other post-operative problems include high rates of dysphagia, gagging and retching, as well as dumping syndrome and gas bloating [ 4 , 5 ]. Rates of failure of redo-Fundoplication is variable in different series from 21% [ 5 ] to 42% [ 6 ] depending on definitions used, type of patients considered and duration of follow-up.…”
Section: Introductionmentioning
confidence: 99%